Early Estimated Glomerular Filtration Rate Trajectories After Kidney Transplant Biopsy as a Surrogate Endpoint for Graft Survival in Late Antibody-Mediated Rejection - Borski, Anita; Kainz, Alexander; Kozakowski, Nicolas; Regele, Heinz; Kläger, Johannes; Strassl, Robert; Fischer, Gottfried; Faé, Ingrid; Wenda, Sabine; Kikić, Željko; Bond, Gregor; Reindl-Schwaighofer, Roman; et al. (Frontiers in Medicine, 2022)
Late antibody-mediated rejection (ABMR) after kidney transplantation is a major cause of long-term allograft loss with currently no proven treatment strategy. Design for trials testing treatment for late ABMR poses a major challenge as hard clinical endpoints require large sample sizes. We performed a retrospective cohort study applying commonly used selection criteria to evaluate the slope of the estimated glomerular filtration rate (eGFR) within an early and short timeframe after biopsy as a surrogate of future allograft loss for clinical trials addressing late ABMR. Study subjects were identified upon screening of the Vienna transplant biopsy database. Main inclusion criteria were (i) a solitary kidney transplant between 2000 and 2013, (ii) diagnosis of ABMR according to the Banff 2015 scheme at >12 months post-transplantation, (iii) age 15-75 years at ABMR diagnosis, (iv) an eGFR >25mL/min/1.73m2 at ABMR diagnosis, and (v) a follow-up for at least 36 months after ABMR diagnosis. The primary outcome variable was death-censored graft survival. A mixed effects model with linear splines was used for eGFR slope modelling and association of graft failure and eGFR slope was assessed applying a multivariate competing risk analysis with landmarks set at 12 and 24 months after index biopsy. A total of 70 allografts from 68 patients were included. An eGFR loss of 1ml/min/1.73m2 per year significantly increased the risk for allograft failure, when eGFR slopes were modeled over 12 months [HR 1.1 (95% CI: 1.01-1.3), p=0.020] or over 24 months [HR 1.3 (95% CI: 1.1-1.4), p=0.001] after diagnosis of ABMR with landmarks set at both timepoints. Covariables influencing graft loss in all models were histologic evidence of glomerulonephritis concurring with ABMR as well as the administration of anti-thymocyte globulin (ATG) at the time of transplantation. Our study supports the use of the eGFR slope modeled for at least 12 months after biopsy-proven diagnosis of late ABMR, as a surrogate parameter for future allograft loss. The simultaneous occurrence of glomerulonephritis together with ABMR at index biopsy and the use of ATG at the time of transplantation - likely representing a confounder in pre-sensitized recipients - were strongly associated with worse transplant outcomes.